Athletic training systems in russia versus us: patenting laws and experiences - Titova, E. V.; Koneva, N. S.; Dubrovin, O. V. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to find the best legal ways to defend the copyrights for the newly designed/ updated athletic training systems/ models. We analyzed for the purposes of the study the existing legal frameworks for the athletic training system patenting in Russia versus the US and some other nations, with an emphasis on the patenting procedures and their deficiencies and challenges.